Validity of the French form of the Somatosensory Amplification Scale in a Non-Clinical Sample - Bridou, Morgiane (Health Psychol Res, 2013)
The SomatoSensory Amplification Scale (SSAS) is a 10-item self-report instrument designed to assess the tendency to detect somatic and visceral sensations and experience them as unusually intense, toxic and alarming. This study examines the psychometric properties of a French version of the SSAS in a non-clinical population and, more specifically, explores its construct, convergent and discriminant validities. The SSAS was completed by 375 university students, together with measures of somatization propensity (SCL-90-R somatization subscale) and trait anxiety (STAI Y form). The results of principal component and confirmatory factor analyses suggest that the French version of the SSAS evaluates essentially a single, robust factor (Somatosensory amplification) and two kinds of somatic sensitivity (Exteroceptive sensitivity and Interoceptive sensitivity). Somatosensory amplification correlated with somatization tendency and anxiety propensity. These results encourage further investigations in French of the determinants and consequences of somatosensory amplification, and its use as a therapeutic strategy.